Sonoelastography Findings in Breast Cancer: Correlation with Molecular Subtypes and Ki-67 Expression - Lydia Purna Kuntjoro; Ignatius Riwanto; Hermina Sukmaningtyas; Yan Wisnu Prajoko; Suhartono Suhartono; Lina Choridah; Endang Mahati; Clarissa Aulia Pravitha (http://dharmais.co.id/, 2026)
Background: Strain elastography is increasingly used as a complementary imaging tool to assess suspicious breast lesions by evaluating tissue stiffness using the strain ratio and elastography score. Owing to the intertumor heterogeneity of breast cancer, this study aimed to investigate the association between elastography findings and tumor proliferation, as indicated by Ki-67 expression, across different molecular subtypes.Methods: This cross-sectional study prospectively collected data from three hospitals, including Dr. Kariadi Hospital, National Diponegoro Hospital, and Ken Saras Hospital. Patients with BI-RADS ultrasound category 4 or 5 lesions confirmed as malignant on histopathology were included. The elastography score was assessed using the Tsukuba elasticity score, while the strain ratio was calculated by comparing the strain elasticity within a lesion with that within the adjacent normal tissue. Independent t-tests and chi-square tests were employed to assess the correlation between elastography findings and gold standard tests, such as molecular subtype and immunohistochemical results. The most significant results were further evaluated for their diagnostic performance. Data were analyzed using SPSS version 25. Results: This study included 29 patients with a mean age of 52.06 ± 11.99 years. The associations between immunohistochemical markers and both the strain ratio and elastography score did not reach statistical significance, possibly due to the limited sample size. Among molecular subtypes, only luminal B demonstrated a significant association with the strain ratio (p = 0.025). Diagnostic evaluation for luminal B yielded a sensitivity of 61.1%, specificity of 81.8%, and an area under the curve (AUC) of 0.689 at a strain ratio cutoff of 4.27.Conclusions: Increased stiffness in the luminal B subtype suggests the potential of strain elastography as a noninvasive indicator of tumor behavior